Employee Morale and Its Influence on Employee Performance in Modern Rice Mill Machinery Manufacturing Industries - G.Senguttuvan; S. Shanmugasundaram (International Journal of Psychosocial Rehabilitation, 2019)
The major goal of this research is to look at employee morale and performance in the Modern Rice Mill Machinery Manufacturing Industries. Motivation, job meaningfulness, organisational commitment, and work pride were included in the concept questionnaire used in this study to assess employee morale. A total of 320 people working in the Modern Rice Mill Machinery Manufacturing Industries were interviewed for the study. Employee morale and performance, according to the findings, are highly correlated.